The Relationship Between Frequency of Participating in Prolanis Exercises and Cholesterol Levels in Hypertension Patients at The Griya Sehat Clinic - Yosepin Galuh Sekar Khinanti; Tasrif Ahmad (Jurnal Biologi Tropis, 2026)
Hypertension is a chronic disease with an increasing prevalence and may lead to various complications, one of which is cardiovascular disorders associated with elevated cholesterol levels. Control of cardiovascular risk factors in patients with hypertension can be achieved through structured physical activity, such as the Chronic Disease Management Program (Prolanis) exercise, while lipid profiles can be evaluated through total cholesterol examination. This study aimed to determine differences in cholesterol levels based on the regularity of participation in Prolanis exercise among hypertensive patients at Griya Sehat Colomadu Clinic. This study was an observational study with a cross-sectional design. The research sample consisted of 26 hypertensive patients who met the inclusion and exclusion criteria. Cholesterol level data were obtained through laboratory examinations, while data on regularity of participation in Prolanis exercise were collected from attendance records. Differences in cholesterol levels based on exercise regularity were analyzed using the Friedman test. The results showed a significant difference between regularity of Prolanis exercise participation and cholesterol levels (p = 0.000), with patients who regularly participated in the exercise having lower cholesterol levels compared to those who participated irregularly or did not participate at all. Most respondents were in the pre-elderly age group with normal body mass index; however, the level of exercise participation varied. It can be concluded that regular participation in Prolanis exercise is associated with differences in cholesterol levels among hypertensive patients at Griya Sehat Colomadu Clinic.